The Development of Information System for Knowledge Management (KM) of Thai Public Organizations according to the Public Sector Management Quality Award (PMQA) - Onkaeo, Sophit (Asian Health, Science and Technology Reports, 2012)
The Development of Information System for Knowledge Management (KM) of Thai Public Organizations according to the Public Sector Management Quality Award (PMQA)